Logging Safety Practices of Chainsaw Workers in the Indonesian State Forest Concession - Ahmad Luthfi Syauqi; Hermudananto Hermudananto; Ratih Madya Septiana; Nunuk Supriyatno (The University of Lampung, 2025)
The forestry industry outside Java continues to rely on chainsaw-based logging in natural forests, a technique that involves significant safety risks due to the size of harvested trees, machine hazards, and challenging environmental conditions. These risks highlight the need for skilled operators and effective Occupational Safety and Health (OSH) systems. This study was conducted at two Indonesian State Forest Concessions in East Kalimantan and examined OSH implementation among chainsaw operators. Data were collected through questionnaires with both qualitative and quantitative components, field observations, interviews, and analysis of company documents, including work plans and safety procedures. The results showed that operator awareness of OSH was very high (85.94%), and support and guidance from managers and foremen also strongly influenced compliance (75.97% and 76.81%, respectively). However, barriers remained (49.46%), particularly in the form of incomplete Personal Protective Equipment (PPE), operator discomfort when using certain PPE, and the absence of structured training. These shortcomings indicate a gap between policy and practice. Addressing these issues requires companies not only to provide complete and comfortable PPE but also to enhance training and actively enforce safety protocols. Strengthening these measures would improve both worker safety and the overall sustainability of forest operations.